Analisis Wacana pada Media Sosial Instagram “Childfree oleh Gitasav” - Damyyanus Tarigan; -, Chairun Nisa; Syarah Ihsani; Lasenna Siallagan; Khadijah; Rouli Simanullang; Fitriani Lubis (IdeBahasa, 2023)
This study aims to describe discource analysis in the social media account of an influencer named Gitasav about childfree. Gitasav's statement on her Instagram was analyzed using the Norman Fairclough (1989) discourse analysis model. This research is qualitative descriptive research, namely research that aims to describe a phenomenon. The data in this study were collected using the read and note method. The data collected will pass three dimensional concept in it; text analysis, discource practice, and sociocultural practice. The result of this study describe discource based on text analysis, discursive practice and sociocultural pratices. Based on the text analysis, that is the ideology which revealed that woman who have children would be the one who was disadvantaged in a household. Based on the analysis of discursive practice, the ideology built in these comments was not fully accepted by society. This reflected the public's response to children's free thought which was not commonly heard in Indonesia. Based on the analysis of sociocultural practices, the childfree discourse uploaded by Gitasav, social life and the thick patriarchal system in Indonesia played a major role in the emergence of public discourse regarding Gitasav's comments.